Beginning iPhone Development - Mark, Dave ; LaMarche, Jeff (Springer, 2017)
Readers will discover how to create programs for the iPhone using Apple's official Software Development Kit (SDK). Readers will learn to design user interfaces using Apple's Interface Builder tool, starting with simple interfaces and progressing to complex, professional-quality multi-view applications. Using a practical step-by-step approach, the readers will see how to implement common iPhone application interfaces and learn about about the Model-View-Controller approach to programming used throughout the iPhone SDK. Readers will also see how to interact with the user through the iPhone's multitouch screen as well as learn how to save data using the iPhone's file system and the embedded SQLite database. The book is packed with information and code samples showing how to exploit all the goodness of the new SDK from the iPhone's built-in accelerometer to the built-in camera and everything in between.